Empathic competences in the professional training of specialists in social work - Savitskaya, Tatyana V.; Shabanova, Natalya E. (University Pedagogical Journal, 2022)
The article is devoted to the problem of the formation of empathic competencies in the process of professional training of students – future specialists in social work. The role of empathy and empathic competencies in the professional training of social specialists is analysed. The level of formation of empathy of students from the 1st to the 4th years, studying the specialty «Social work (according to directions)» was revealed. The ways of formation of empathic competencies are determined.
Keywords: empathy; empathic competences; social sphere; social work specialist; professional quality